2021
DOI: 10.1029/2021ja029537
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Response to the December 14, 2020 Total Solar Eclipse in South America

Abstract: Solar eclipses are known to generate changes throughout the atmosphere, from the surface of the Earth to the top of the ionosphere (Anderson, 1999). Because these changes occur as a result of the passage of the shadow of the Moon, which can be accurately predicted, the eclipse can be used as a controlled atmospheric experiment (Clayton, 1901). Since many atmospheric processes are still not well understood, solar eclipses provide valuable data to further understand atmospheric phenomena.One atmospheric effect p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…In this study, the authors assumed that during the eclipse totality, a 30% of the coronal radiation remains, similarly as in previous studies (Reinisch et al, 2018;Bravo et al, 2020). Although a C4-class solar flare was detected on the day of the eclipse, no significant ionospheric impact was observed during this day, as indicated in previous studies of this event (Gómez, 2021;de Haro Barbás et al, 2022). Therefore, in this study, we consider that no significant contribution modified the overall ionospheric response to the eclipse, allowing a direct comparison to the model prediction results.…”
Section: Ionospheric Modelsupporting
confidence: 63%
See 1 more Smart Citation
“…In this study, the authors assumed that during the eclipse totality, a 30% of the coronal radiation remains, similarly as in previous studies (Reinisch et al, 2018;Bravo et al, 2020). Although a C4-class solar flare was detected on the day of the eclipse, no significant ionospheric impact was observed during this day, as indicated in previous studies of this event (Gómez, 2021;de Haro Barbás et al, 2022). Therefore, in this study, we consider that no significant contribution modified the overall ionospheric response to the eclipse, allowing a direct comparison to the model prediction results.…”
Section: Ionospheric Modelsupporting
confidence: 63%
“…Measurements of multiple ground-based instruments along the continent (i.e., ionosonde stations, an Incoherent Scatter Radar, and GNSS receiver networks) and satellites (i.e., Swarm-A) are used to evaluate the accuracy of simulation results, providing a testbed scenario to determine the accuracy of the ionospheric prediction model under total eclipse conditions. In addition, the results of this evaluation are compared to the ionospheric response to the 2 July 2019, solar eclipse that occurred in the same geographical area (Bravo et al, 2020;Jonah et al, 2020;Maurya et al, 2020) and previous studies that evaluated the ionospheric response to the 14 December 2020, solar eclipse (e.g., Gómez, 2021;Meza et al, 2021;Shrivastava et al, 2021;de Haro Barbás et al, 2022;Resende et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they expected ionospheric changes in the conjugate hemisphere during this event. Gómez (2021) has reported, modeled, and interpreted the Gravity Waves (GWs) perturbations in the ionosphere to this solar eclipse along the totality path. The author detected the wave‐induced phenomena on Total Electron Content (TEC) measurements near the Southern Andes in the Patagonia region and showed a good agreement between the SAMI3 ionospheric model predictions and the TEC data for this solar eclipse event.…”
Section: Introductionmentioning
confidence: 99%
“…The Total Solar Eclipse (TSE) that occurred on 14 December 2020 is a great opportunity to evaluate the effects on the geomagnetic field variations and the plasma density in South America. Recent studies have reported the observations and predictions of the atmospheric and ionospheric effects of this eclipse event (de Haro Barbás et al, 2022;Gómez, 2021;Martínez-Ledesma et al, 2020;Resende et al, 2022;Shrivastava et al, 2021). Using the SUPIM-INPE (Sheffield University Plasmasphere-Ionosphere Model-INPE) model, Martínez-Ledesma et al (2020) first predicted the ionospheric response to the TSE that occurred on 14 December 2020.…”
mentioning
confidence: 99%
“…They modified the SUPIM to simulate the behavior of solar obscuration on the ionosphere at low and middle magnetic latitudes. Gómez [45] compared TEC variations using 46 GNSS stations around the path of the umbra of the eclipse to that predicted by the SAMI3. The results showed that TEC perturbations after totality could be triggered by orographic gravity waves (oGWs) not related to the eclipse.…”
Section: Introductionmentioning
confidence: 99%